Ten-Year Results From the Natrelle 410 Anatomical Form-Stable Silicone Breast Implant Core Study - Maxwell, G. Patrick; Van Natta, Bruce W.; Bengtson, Bradley P.; Murphy, Diane K. (Aesthetic surgery journal, 2015)
Background Silicone breast implants have long been used for breast augmentation and reconstruction. During this time, these medical devices have gone through a number of modifications to improve their safety, quality, and clinical outcome performance. Objectives The authors conducted a 10-year study to determine the safety and effectiveness of Natrelle 410 silicone breast implants. Methods This prospective, multicenter study enrolled 941 subjects who were undergoing either augmentation, augmentation revision, reconstruction, or reconstruction revision. Data on complications, reoperations, explantations, and subject satisfaction were collected at annual clinic visits, and one-third of subjects underwent biennial magnetic resonance imaging (MRI) to screen for implant rupture. The authors used the Kaplan-Meier estimator to calculate risk rates for local complications, reoperations, and explantations. Results Capsular contracture rates increased approximately 1% per year from the previously reported 6-year rates. The rates were significantly lower than those from the Natrelle round gel core study. The overall rate of confirmed ruptured implants in subjects who underwent MRI was 5.7%. Eleven late seromas were reported. The most common reason for explantation was a subject requesting a size or style change. Satisfaction rates remained high through 10 years, with most subjects saying they were somewhat or definitely satisfied with their implants. Conclusions This 10-year prospective trial demonstrated the long-term safety and effectiveness of Natrelle 410 anatomical form-stable implants. The complication rates were low and the satisfaction rates were high. Level of Evidence: 1 Therapeutic